What is Morality? Pascal's Heartfelt Answer - Giorgio Baruchello (Nordicum-Mediterraneum, 2014)
Despite his enduring fame as a scientist and a thinker, Blaise Pascal's moral philosophy has received very little attention by modern Anglophone ethicists, who have written instead endless volumes on the epistemology of his wager—itself a piece of apologetics and an early example of game theory. They have labelled Pascal a ‘philosopher of religion’ and pretty much left him there, as marginal as religion itself seems to be these days. Yet, Pascal did have a moral philosophy of his own and one that can help us answer the question ‘what is morality?’ from the perspective of lived personal experience. It is not an easy one to detect, for it is scattered across his unsystematic maxims, short reflections and aphorisms, themselves scattered across a number of differing manuscripts. Reconstructing and outlining it is the chief aim of my paper.